ANALYZING THE IMPACT OF BUILDING SECTOR ENERGY POLICIES AND REGULATIONS ON ENERGY DEMAND IN SRI LANKA - HETTI GODAGE GAYASHAN KULATHUNGA (Graduate School of International Studies Ajou University, 2024)
This study employs two different methodologies to evaluate the future development of Sri Lanka's building industry. First, it assesses how building floor area and energy consumption will increase over the course of the next three decades under three different population projections. The second goal is to evaluate how well various energy efficiency regulation implementation tactics contribute to increases in energy demand and decreases in emissions. To evaluate these scenarios, the Energy Modelling Lab at Ajou University developed an extended model of GCAM called GCAM-EML. The UN's population projections for Sri Lanka are used in the study, which makes three assumptions about population projection scenarios: "Lower," "Reference," and "Upper." According to simulation results, the nation's total building floor area will increase by 51%, 62%, and 73% between 2020 and 2050 under the "Lower," "Reference," and "Upper" population scenarios, respectively. This implies that during the next thirty years, Sri Lanka's building industry will grow significantly. Additionally, the findings demonstrate that, in all three population projection scenarios, the country's primary energy demand, total CO2 emissions from end-use sectors, and electricity will double by 2050. Furthermore, it is anticipated that the demand for electricity will increase fourfold between 2020 and 2050, pointing to a shift toward cleaner energy sources. In examining how building energy regulations affect the growth of the building sector's energy demand, it is anticipated that Sri Lanka's population will rise gradually to a peak of 22.279 million by 2035, after which it will start to decline and reach 21.185 million by 2050. According to the simulation results, if the energy efficiency building code is not applied, Sri Lanka's total primary energy demand will rise by 2.04 times in comparison to the current situation. Nonetheless, the application of EEBC at both low and high compliance rates indicates that by 2050, commercial sector buildings could save a total of 9,330.24 GWh to 15,778.66 GWh of electricity. Furthermore, extending the application of energy efficiency regulations to the residential sector may save between 41,562.16 and 69,445.94 GWh in total. According to the study, cumulative CO2 emissions could be lowered by the building sector's application of efficiency regulations by 0.63 to 5.44 million tons of carbon dioxide. The study highlights how important energy regulations will be in shaping Sri Lanka's energy landscape going forward. Policymakers, energy stakeholders, and researchers can use the research's insights into the effectiveness of building-related policies to help them develop sustainable energy strategies. With Sri Lanka's construction industry growing rapidly, it is imperative to slow down the rise in energy consumption, particularly for electricity, by enacting strong building energy policies. The findings back up proactive energy regulations as a way to steer Sri Lanka in the direction of a more sustainable and energy-efficient future while maintaining a balance between economic growth and responsible energy consumption. Key Words: GCAM-EML, GCAM, Building Energy Code, Energy Demand, Emission Reduction, Energy Regulation.
학위논문(석사)--융합에너지학과,2024. 2
Keywords: Building Energy Code; Emission Reduction; Energy Demand; Energy Regulation; GCAM; GCAM-EML